How Jordan and Saudi Arabia are avoiding a tragedy of the commons over shared groundwater. Issue 7 (4th July 2017) - Müller, Marc F.; Müller‐Itten, Michèle C.; Gorelick, Steven M.
Abstract: Transboundary aquifers are ubiquitous and strategically important to global food and water security. Yet these shared resources are being depleted at an alarming rate. Focusing on the Disi aquifer, a key nonrenewable source of groundwater shared by Jordan and Saudi Arabia, this study develops a two‐stage game that evaluates optimal transboundary strategies of common‐pool resource exploitation under various assumptions. The analysis relies on estimates of agricultural water use from satellite imagery, which were obtained using three independent remote sensing approaches. Drawdown response to pumping is simulated using a 2‐D regional aquifer model. Jordan and Saudi Arabia developed a buffer‐zone strategy with a prescribed minimum distance between each country's pumping centers. We show that by limiting the marginal impact of pumping decisions on the other country's pumping costs, this strategy will likely avoid an impeding tragedy of the commons for at least 60 years. Our analysis underscores the role played by distance between wells and disparities in groundwater exploitation costs on common‐pool overdraft. In effect, if pumping centers are distant enough, a shared aquifer no longer behaves as a common‐pool resource and a tragedy of the commons can be avoided. The 2015 Disi aquifer pumping agreement between Jordan and Saudi Arabia, which in practice relies on a joint technical commission to enforce exclusion zones, is the first agreement of this type between sovereign countries and has a promising potential to avoid conflicts or resolve potential transboundary groundwater disputes over comparable aquifer systems elsewhere. Key Points: Distance and groundwater exploitation cost disparities drive tragedies of the commons for shared aquifers Common‐pool effects are limited when the pattern of groundwater depletion resembles an egg‐carton rather than a communal bathtub The no‐pumping buffer zone in the 2015 agreement between Jordan and Saudi Arabia avoids common‐pool overdraft through at least 2075